Diabetes mellitus and considerations for dentistry - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (Livre de Lyon, 2023)
Diabetes mellitus (DM, diabetes) is a chronic metabolic condition characterized by hyperglycemia caused by an absolute or relative deficiency of insulin, a hormone secreted by the β- cells of the pancreas, as well as disorders in protein, fat and carbohydrate metabolism, capillary membrane changes and accelerated atherosclerosis. (1-10) In other words, diabetes is defined as an endocrine disorder that can occur in the absence of insulin and is characterized by hypofunction of the islets of Langerhans βcells, resulting in excessive increase of blood glucose levels and excretion of glucose from the urine. With this metabolic disorder, the pancreas may produce insufficient insulin, or peripheral tissues may become insulin resistant. (1,4,6,7)
Keywords: Diş Hekimliği; Klinik Bilimler; Sağlık Bilimleri; Dentistry; Clinical Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry